ANALYSING THE LOOPHOLES ON ESTATE ADMINISTRATION OF CRYPTOCURRENCY IN MALAYSIA: SHARIAH AND LAW PERSPECTIVES (International Journal of Islamic Business, 2022)
The recognition of cryptocurrency as digital assets in Malaysia under the purview of security governed by the Securities Commission of Malaysia contributed to cryptocurrency's positive acceptance, with evidence that the number of cryptocurrency users is growing. Nonetheless, due to the unique characteristics of cryptocurrency, the lack of legal regulation on cryptocurrency inheritance will have an impact on crypto estate administration. Apparently, the law on cryptocurrency in Malaysia is still in its infancy, and the existing issue of frozen estate in Malaysia, which is constantly increasing, prompted the researchers to investigate potential loopholes in cryptocurrency estate administration from a legal and shariah standpoint. The study conducts content analysis by examining the relevant statutories, such as “the Probate and Administration Act 1959, the Capital Market Service Act 1997, the Capital Market and Services (Prescription of Securities) (Digital Currency and Digital Token) Order 2019, Shariah Resolutions and Fatwas in Malaysia”, other literatures related to cryptocurrency estate administration. As a result, there are legal loopholes in cryptocurrency estate administration in Malaysia that prevent cryptocurrency from being inherited by the entitled beneficiary. The issue of cryptocurrency inheritance may arise in the near future; thus, this study provides policy implications to the Malaysian regulators to solve the highlighted lacuna as well as social implications to the Malaysian society to consider cryptocurrency in their inheritance planning.